Legal Certainty in the Transformation of Land Sale Agreements into Debt Relationships - Depi Shinta Uli Sembiring; Orpa Juliana Nubatonis; Dhesy A. Kase (Yayasan Pendidikan Islam Almatani, 2026)
This study examines the legal implications of transforming a land sale and purchase agreement into a debt relationship through a court-ratified settlement deed, viewed from the perspective of legal certainty. The purpose of this research is to analyze the legal validity of such transformation, assess the extent to which legal certainty is upheld, and evaluate the protection afforded to the parties, particularly the seller and their heirs. This research employs a normative legal research method using statutory, case, and conceptual approaches. Primary and secondary legal materials were analyzed descriptively and analytically by applying the theory of legal certainty proposed by Satjipto Rahardjo and the theory of justice developed by John Rawls. The findings indicate that the transformation of the land sale agreement into a debt agreement through a settlement deed lacks substantive validity, as it does not fulfill the legal requirements of novation under Article 1413 of the Indonesian Civil Code. Although the settlement deed provides formal legal certainty through judicial endorsement, it fails to ensure substantive legal certainty and equitable legal protection, resulting in prolonged legal disputes and legal ambiguity for the parties involved. The originality of this research lies in its critical examination of court-sanctioned settlement deeds that alter the substance of authentic land sale agreements without prior annulment, highlighting the tension between formal legal certainty and substantive justice in Indonesian contract law.